QUALITY ASSESSMENT OF SHEREHILLS DAM WATER FOR DRINKING AND IRRIGATION PURPOSES IN JOS, NIGERIA - Oiganji, E.; Onwuegbunam , N. E.; Onwuegbunam, D. O.; Abok, B. A. (FUDMA JOURNAL OF SCIENCES, 2023)
This study was carried out to assess physiochemical parameters at different sections of the Sherehills dam reservoir situated in Jos North Area of Plateau State. Water samples were collected in three (3) different locations namely; upper, center and lower section, and analyzed at the Bauchi State Water Quality laboratory. The result of the analyzed parameters when compared with the standard water quality of NESREA (2011) and NSDWQ (2015) were within the permissible limits for irrigation purposes; for drinking, the turbidity and color were high. Turbidity and color do not have much effect on plant development and growth but with regards to consumption by humans, it must be treated with activated carbon filter and alum flocculation. There is need for periodic quality analysis of water for drinking and irrigation
Keywords: Dam, Sherehills, parameters, physiochemical and Water quality